Educational Background, Work Experience and Infrastructure Impact on Health and Safety Standards Performance at PT ABC - East Java Operations Area - Daniati, Kristina; Kholil, (Archives of Business Research, 2022)
PT ABC is a national oil company focusing on upstream activity, exploration, development and exploitation that enforces occupational health and safety standards through the Health Safety Environment Management System (HSEMS) with systematic efforts through the Operational Excellent framework. Based on the preliminary research conducted, it was found that the performance of PT ABC's occupational health and safety standards had not reached the maximum value, therefore the research was conducted with the aim of knowing and analyzing the Influence of Educational Background, Work Experience and Infrastructure on the Achievement of Health and Safety Standards with Employee Information Literacy as Intervening Variables. The research method used quantitative research method. The study population was 120 employees in East Java Operation, with a sample of 90 respondents. Data collection uses surveying, observation and documentation techniques. Data analysis using Outer Model (Convergent Validity, Discriminant Validity, Composite Reliability, Average Variance Extracted, Cronbach Alpha) and Inner Model (Coefficient of Determination, Predictive Relevance, Goodness of Fit (Gof) index Test, Reliability Test). Hypothesis testing used full analysis of Structural Equation Modeling (SEM) models with smartPLS. The results showed that: 1)Educational background through information literacy affects the achievement of K3 Standards at PT ABC (2,028); 2)Work experience through information literacy affects the achievement of K3 standards at PT ABC (t = 2,190); and 3)Infrastructure through information literacy has no effect on the achievement of K3 Standards at PT ABC (t = 0.008).